2021
DOI: 10.1111/epi.16930
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy, antiepileptic drugs, and the risk of major cardiovascular events

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 38 publications
(94 reference statements)
1
33
0
Order By: Relevance
“…Two other population-based studies have examined if enzymeinducing agents increase the long-term risk of cardiovascular events but yielded conflicting results. 67,68 There have been speculations that valproic acid may reduce the risk of cardiovascular disease by inhibiting the gene histone deacetylase 9, which has been associated with large artery disease. 69 While there is some evidence that patients receiving valproic acid have a lower risk of cardiovascular events compared with enzyme-inducing drugs, 69,70 it has also been associated with increased carotid artery intimal-medial thickness (a marker for large artery disease and stroke).…”
Section: Potential Long-term Effects On Vascular Riskmentioning
confidence: 99%
“…Two other population-based studies have examined if enzymeinducing agents increase the long-term risk of cardiovascular events but yielded conflicting results. 67,68 There have been speculations that valproic acid may reduce the risk of cardiovascular disease by inhibiting the gene histone deacetylase 9, which has been associated with large artery disease. 69 While there is some evidence that patients receiving valproic acid have a lower risk of cardiovascular events compared with enzyme-inducing drugs, 69,70 it has also been associated with increased carotid artery intimal-medial thickness (a marker for large artery disease and stroke).…”
Section: Potential Long-term Effects On Vascular Riskmentioning
confidence: 99%
“…49,50 False positives can lead to the inappropriate prescription of AEDs that result in adverse effects or worsening symptoms. 50,51 This issue is compounded by societal inequities, as 80% of patients with epilepsy are amongst low to middle-income populations, and 75% of them do not receive any treatment. 6 The treatment gap can be attributed to inequities in distribution and access to services, stigma associated with the disease, lack of sufficient expert resources (neurologists), and an inadequate supply of modern AEDs.…”
Section: Perspective and Future Workmentioning
confidence: 99%
“… 1 , 2 In a recent study, patients with epilepsy taking antiseizure medications (ASMs) had a 58% higher adjusted risk of having a major cardiovascular event than matched controls. 3 Cardiac complications in epilepsy include (1) Seizure-related events like ictal bradycardia, asystole, ventricular tachycardia, ventricular fibrillation, atrial fibrillation, myocardial infarction, and Takotsubo cardiomyopathy (especially with tonic-clonic convulsions), (2) Epilepsy-related outcomes such as cardiac autonomic dysfunction and the “epileptic heart,” and (3) Treatment-related events like ASM-induced arrhythmias and hyperlipidemia. 1 Some sodium channel blocking (SCB) ASMs can contribute to cardiac arrhythmias, and the U.S. Food and Drug Administration recently asked manufacturers of all SCB ASMs for additional research after announcing warnings about the theoretical risk of lamotrigine.…”
Section: Commentarymentioning
confidence: 99%
“…8,9 In contrast to the current study, another recent study found no difference in cardiovascular events between EI and non-EI ASM groups. 3 Methodological differences included a smaller cohort of 10,241 epilepsy patients, use of a more liberal definition of EI ASM exposure, and not tracking the dose of each ASM prescription. An important difference was that the epilepsy patients were followed for a mean of 6 (maximum 15) years compared to a median of 9 (maximum 29) years in the study by Josephson et al 5 This may account for the lack of difference between the 2 groups, because the latter study found that the cumulative hazard was only marginally higher over the first 8 to 10 years, but then there was continued annual divergence by more than 1% through year 25 suggesting a chronic, cumulative effect with persistent use of EI ASMs.…”
mentioning
confidence: 99%